Pengembangan dan Profil Farmakokinetik Senyawa Turunan Pirazolo-(3,4-D)-Pirimidin Sebagai Inhibitor Mer Secara Insilico - Nursalam Hamzah; Nurmaya Efendi; Muh. Hidayat (Jurnal Farmasi UIN Alauddin Makassar, 2014)
The Mer receptor is an important target for development of molecular probes in oncology because just expressed by T cell Acute Leukemia Lymphboblastic and not expressed by T-cell normal and a ATP kinase competitive inhibitor. The purpose of this research is development derivate Pyrazolo-[3,4-D]-pyrimidin then choose candidate active and selective chemicals for Mer receptor to be a treatment for acute leukemi lymphoblastic by insilico. Procedures are began with modelingand geometry optimization of molecular structure which made by HyperChem 8.0. Geometry optimization was performed by Ab initio method. QSAR descriptors were calculated by MOE 2009. The next step is determine pharmacokinetic profile with AdmetSAR and DemPred. Based on pharmacokinetic predictions overall koefisian compounds have the same choice 1.0000 on human intestinalabsorption can be absorbed properly. the most well permeabiltas Caco2 cells are compounds 008 and 115. Compounds 008 and 115 also has the lowest coefficient on thepenetration of blood brain barrier. Compounds 008 and 115 have the smallest volume of distribution is 2.400352 L / kg means that the volume of the compounds 008 and 115.Compounds with the best clearance of compounds 001 and 111 with a clearan  of 2.058811 ml / min / kg.